Pluralism of Sasak Puppet: A Study Of Intercultural Communication On Lombok Island - Apriaman, Abdul Latief; Jamaluddin; Wahid, Abdul (Universitas Islam Negeri (UIN) Mataram, 2025)
Sasak Puppet is one of the traditional performing arts that is believed to be a medium for broadcasting Islam on Lombok Island. This conclusion is strengthened by using scripts Serat Menak as the performance material. Serat Menak is based on the Persian story Qisa El Amir Hamza, with the central character Amir Hamzah, the uncle of the prophet Muhammad SAW. In practice, the Sasak Puppet performance in Lombok is played not only by Muslim puppeteers but also by Hindu puppeteers. Sasak Puppet is also enjoyed by the Muslim community and the Hindu community in Lombok; even the Sasak Puppet performance is also held in a temple, a place of worship for Hindus. This study describes the existence of pluralism in the Sasak Puppet performance, starting from the performance material and the interaction of the puppeteers and the Sasak Puppet enthusiasts both in the performance space and in everyday life outside the performance. As a product of intercultural communication, Sasak Puppet deserves to be a reference for the public who wants to build pluralism in a multicultural society.